Inhibition, by a protease inhibitor, of the solubilization of the F1-portion of the Mg2+-stimulated adenosine triphosphatase of Escherichia coli. - Cox, G B (1978)
The effects of two protease inhibitors on the solubilization of the membrane-bound Mg2+-adenosine triphosphatase (Mg-ATPase) of Escherichia coli were investigated. p-Aminobenzamidine prevented the solubilization of the Mg-ATPase during treatment of membranes with low-ionic-strength buffers containing ethylenediaminetetraacetic acid. p-Aminobenzamidine did not prevent subsequent solubilization of the Mg-ATPase by treatment of the membranes with chloroform. This method of solubilization yielded a preparation of similar apparent molecular weight but with a 10-fold-increased specific activity as compared with the Mg-ATPase solubilized by washing with low-ionic-strength buffer. However, in contrast to the latter preparation, the chloroform-solubilized Mg-ATPase did not reconstitute ATP-dependent energization of stripped membranes, which were prepared by low-ionic-strength washing in the absence of p-aminobenzamidine. Another protease inhibitor, epsilon-amino-n-caproic acid, did not effect the solubilization of the Mg-ATPase, but did inhibit the loss of activity occurring during concentration, by ultrafiltration, of the Mg-ATPase solublized by the low-ionic-strength treatment.